O crescimento e desenvolvimento sócio-econômico das cooperativas agroindustriais do Oeste do Paraná - Ilha, Paulo César da Silva (2010)
This search, whose title is "The growth and socio-economic development of agribusiness cooperatives in the West of Parana State", presents a new methodology for analysis of cooperatives. Considering that these developments differ from any business because it was there is of principles and doctrines aspects that distinguish them from other companies, especially those related to the inter-cooperation and concern for the community. It arose from the assumption that "It is likely that the agribusiness cooperatives in the west of Parana state are suitable for strategic management of inter-cooperation for development, generating economic and social growth and contributing to regional economic development." The first analysis examined the relationships of inter-cooperation that these cooperatives have with each other. Subsequently, we examined their growth, considering the Gross Sales, Fixed Assets, Equity, increasing the number of cooperative members and employees, increase within the last ten years. Then there is the efficiency to manage the Capital, to calculate the Economic Value Added, to evaluate whether the cooperatives add value or destroy the capital of its members and financial independence, to know whether they have sufficient capitalization to cope with new investments without compromising its operating results. Finally, we sought whether the cooperatives contribute to the growth of the municipalities where they are located. With all these perspectives of analysis, it is concluded that the cooperatives should get tested for inter increase and improvements in its management to do with the new requirements of market competition, satisfying serve their members in a better way and contribute more to the growth of the communities in which they are inserted.